Metal-polyethyleneimine-activated carbon interaction parameter at equilibrium adsorption capacity - Yin, C.Y.; Aroua, M.K.; Daud, W.M.A.W. (Journal of Applied Sciences, 2010)
A simple interaction parameter (IPEI) for adsorption of metal ions on polyethyleneimine (PEI)-impregnated activated carbon (AC) has been determined and compared. It is used to elucidate and compare the degree of interaction between metal and surface of PEI-impregnated AC.